2013
DOI: 10.1002/pen.23658
|View full text |Cite
|
Sign up to set email alerts
|

Bubble nucleation in nonpressurized polymer foaming systems

Abstract: The mechanism of bubble nucleation in the foaming process under atmospheric pressure is investigated in the present study. The experimental observations using a plastic‐foaming visualization setup revealed two stages of nucleation, primary nucleation in interstitial regions and secondary nucleation in the polymer melt, which followed the sintering and densification of the polymer matrix. Statistical analysis of the evolving cellular structure during the nucleation stage was used to study the significance of rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
(45 reference statements)
1
19
0
Order By: Relevance
“…It was observed that low viscosity and melt elasticity for a gas‐laden matrix allowed a larger number of bubbles to survive and grow larger than the critical nucleus. A detailed explanation of the effect of rheology on the nucleation behavior of polyethylene materials has been discussed in our previous work . The trend of decline in bubble density after nucleation was notably similar for all resins; however, resins with higher melt viscosity/elasticity resulted in lower rate of bubble density reduction.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…It was observed that low viscosity and melt elasticity for a gas‐laden matrix allowed a larger number of bubbles to survive and grow larger than the critical nucleus. A detailed explanation of the effect of rheology on the nucleation behavior of polyethylene materials has been discussed in our previous work . The trend of decline in bubble density after nucleation was notably similar for all resins; however, resins with higher melt viscosity/elasticity resulted in lower rate of bubble density reduction.…”
Section: Resultsmentioning
confidence: 80%
“…The difference between numerical and experimental results can be explained by the effect of viscosity during the nucleation stage. Our previous experimental and theoretical studies showed that higher viscosity could impede the number of nuclei survived during the nucleation stage in the foaming system . Because of lower nucleated bubble density and higher availability of foaming gas in the polymer matrix, foams produced by resins with higher viscosity showed in larger average bubble size during all stages of the foaming process.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In our case, the diffusion process is in the opposite direction from the bubble, which is supposed to be nucleated around the CBA particle, towards the polymer matrix. Recently Emami et al analyzed the bubble nucleation in non‐pressurized foaming CBA systems starting from solid materials, composed of PP and CBA powders as in our experiments. It was observed that the nucleation process proceeded in two distinct stages, namely primary and secondary nucleation.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Commercial interest in polymeric foams has been increased due to new emerging applications and the ability to foam a variety of polymeric materials or composites. Despite their success, the continuous growth in research of foamed polymers into new markets depends on the ability to enhance control over its mechanical structure and performance (Emami et al, 2014).…”
Section: Introductionmentioning
confidence: 99%